The Role of the World Trade Organization in Shaping International Relations and Trade Diplomacy - Sari, Avid Leonardo; Irwandi; Gusmailina; Judijanto, Loso; Hendarto, Totok (GoAcademica Research & Publishing, 2024)
This article embarks on an extensive literature review to dissect the pivotal role of the World Trade Organization (WTO) in sculpting international relations and trade diplomacy. Recognizing the WTO as a cornerstone in global economic governance, the paper elucidates how this institution influences foreign policy strategies and fosters economic cooperation among nations. Through a meticulous analysis of scholarly articles, official WTO documents, and historical trade agreements, the study highlights the evolution of WTO's influence in steering international trade norms and resolving disputes. It underscores the dynamic interaction between WTO policies and national interests, mapping out how these interactions have shaped economic alliances and rivalries. The review further delves into the critical discourse surrounding WTO's efficacy and the challenges it faces in the modern geopolitical landscape, including emerging trade wars and protectionist trends. By weaving together different strands of academic thought, the paper aims to present a nuanced understanding of WTO's multifaceted impact on global trade dynamics and international diplomacy. The findings of this review are intended to inform policymakers, academicians, and trade practitioners about the intricate interplay of trade, diplomacy, and international relations within the ambit of the WTO.